How Do Public Relations Practitioners Experience Technostress? Voices of PR Practitioners in a Hyperconnected World - Riddell, Diane (Université d'Ottawa / University of Ottawa, 2025)
This research examined the lived experience of public relations (PR) practitioners who use Information and Communication Technologies (ICTs) such as smartphones and laptops for work purposes, not only during the regular work day but also after hours and on weekends. Through the voices of the practitioners themselves, experiences of stress, work-life balance, satisfaction, and other factors were studied. This research followed a critical approach focused on the hyperconnected, hypermodern society in which everything is socially accelerated. Research questions examined the experience of technostress of public relations practitioners, the strategies practitioners used to resist or emancipate themselves from the constant call of technology for work purposes, and what this means for PR practitioners and the practice of PR. Practitioner views on the right to disconnect were also probed and this research was able to gather reflections from practitioners on their experience of working during the COVID-19 pandemic. Mixed methods consisted of an online survey (N=123) with PR practitioners followed by interviews (N=25) with a sub-set of survey respondents. This study found that PR practitioners appreciated the flexibility that remote and hybrid forms of work have brought to the workplace. However, the range of strategies applied by practitioners to get relief or free themselves from the constant call of connection was limited in many cases. Practitioners felt better resourcing, better support and role modelling from senior leadership, stronger boundaries, as well as a shared understanding of what constituted a crisis needing communications support outside of regular working hours would support practitioners. These findings contribute to public relations scholarship by focusing on the voices of PR practitioners in Canada and the experiences they face with ICTs and their work.
Keywords: Public relations; Technostress; ICTs; Information and communication technologies; Right to disconnect